REENCOUNTER WITH YOUR "INTERIOR CHILD": the plenitude of being-itself in the phenomenological-existential perspective - Marcia Pereira da Silva Cardoso, Mariza; Tinoco Boechat, Ieda (LINKSCIENCEPLACE, 2026)
This article seeks to analyze the "rescue" of children’s experiences to integrate the personal experience of the adult, as a possibility for him to welcome himself in his totality and become more aware of himself and the world. The problem is thus questioned: what leads a person to direct closure and the method to restrict their freedom to realize themselves? By means of bibliographic research, authors such as Erthal (2013), Korczak (1981), Sapienza (2008) and Forghieri (2004), Crema (1995) and others, can verify that letting this child come and recognizing The total person can promote the restoration of the desire to realize himself, seeking an expansion of possibilities and an updating of potentialities, that is, of his becoming. In this confrontation, through authentic choices, one can live something new, walking between pain and happiness, with more confidence.